(untitled) (Revista de História Regional, 2008)
This article tries to understand the readings of Euclides da Cunhas Os Sertões, which the members of the Centro Cultural Euclides da Cunha, in Ponta Grossa, in Southern Brazil, did along the 1940s and 50s. The analysis is centered on the different understandings of Brazilian nationality, regional identities, and gathering around the ideals of race, nation and literature in order to form an interpretative community which shared the representations about these themes.